Organizing Committee - Mouzouropoulos, Theseas (My University, 2026)
The aspiration of the Cyprus Poster Triennial (CPT) is to establish a graphic design event in the Mediterranean at a place that, on the one hand, can function as a bridge between East and West, and on the other, can bring together designers from all over the world with a variety of perspectives to meet and celebrate the wondrous power of the graphic poster.